Baldassare Longhena and Venetian baroque architecture - Hopkins, Andrew (Yale Univ. Press, 2012)
Venetian Baroque -- S. Maria della Salute -- Gradus ad Sapientiam -- Cult and Memory -- Prestige Palaces -- The Outsider -- Appendix One: Life and Works -- Appendix Two: Critical Appreciation -- Appendix Three: List of Works